A novel percutaneous nephrolithotomy (PCNL) set: The ‘Economical One-shot PCNL Set’ (Ecoset) - Necmettin Penbegul (Taylor & Francis Group, 2017)
Objectives: To suggest a novel disposable percutaneous nephrolithotomy (PCNL) set that we named the ‘Economical One-shot PCNL Set’ (Ecoset), which consists of a single 30-F dilator, 30-F sheath, and 8-F polyurethane dilator, as use of a ‘one-shot’ dilatation technique during PCNL is becoming widespread. Patient and methods: The medical records of 42 patients with kidney stones who had undergone ‘one-shot’ PCNL from February 2014 to June 2016 were retrospectively reviewed and analysed. Demographic data, as well as the stone size, radiation exposure time, operation time, hospitalisation duration, rate of treatment success and complications, were recorded. Results: The mean (SD, range) age of the patients was 44.43 (16.54, 11–72) years. The mean (SD) stone size was 35.12 (17.53) mm. The mean (SD) operation time was 54.58 (22.24) min. The mean (SD) fluoroscopic screening time was limited to 154.72 (117.48) s. Treatment success was achieved in 32 (76%) patients. The mean (SD) hospital stay was 3.09 (0.75) days. None of the patients had any major complications. Bleeding requiring blood transfusion was required in three patients. The cost of a disposable dilatation set for a single PCNL operation with a balloon set, a standard Amplatz set, or an Ecoset is ∼$137, $120, or $27 (American dollars), respectively. Conclusions: The one-shot dilatation technique using the Ecoset for PCNL can be feasibly, safely, and effectively performed in almost every adult patient. The Amplatz dilator set and balloon dilator set have the disadvantage of relatively high cost, whereas the Ecoset is the cheapest ‘disposable set’ that can be used during PCNL surgery.